LANGUAGE - SPEECH MEDIA (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is about the place and importance of language and speech in world linguistics, and their specific functions. In the article, you will get to know the views and opinions of different scientists about language and speech, the abstract-concrete characteristics of language and speech. You will be able to consider the relative independent units of the style, as well as the specific subtleties of the language.